Teachers’ Perspectives on Interpreting Services - David Uwumborlame Bunbun (Universitas Pendidikan Indonesia (UPI), 2024)
The study sought to explore teachers’ perspectives on interpreting services in the salvation army school for the Deaf. The study was guided by two objectives which include finding out Teachers’ views on the academic impact of interpreting services; Investigate strategies that are used to maximize interpreting services The study employed a case study design. The semi-structured interview guide was used to gather data for the study. The purposive sampling technique was used to select the teachers. The sample size of the study was ten teachers within the Salvation Army School for the Deaf in the Central Region of Ghana. Most of the respondents perceived that the academic impact of interpreting services includes effective communication and access to communication. Strategies used to maximize interpreting services were modern technology, workshop training, and motivation. The study, therefore, recommends that the Government of Ghana should motivate interpreters through awards and allowances, and ICT tools that aid interpreting services should be made available and accessible. The Government should periodically organize training sessions to equip interpreters with new vocabulary.